2010
DOI: 10.1098/rsbl.2010.0701
|View full text |Cite
|
Sign up to set email alerts
|

Eastward from Africa: palaeocurrent-mediated chameleon dispersal to the Seychelles islands

Abstract: Madagascar and the Seychelles are Gondwanan remnants currently isolated in the Indian Ocean. In the Late Cretaceous, these islands were joined with India to form the Indigascar landmass, which itself then split into its three component parts around the start of the Tertiary. This history is reflected in the biota of the Seychelles, which appears to contain examples of both vicariance- and dispersal-mediated divergence from Malagasy or Indian sister taxa. One lineage for which this has been assumed but never th… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

6
63
0

Year Published

2012
2012
2016
2016

Publication Types

Select...
7

Relationship

3
4

Authors

Journals

citations
Cited by 63 publications
(70 citation statements)
references
References 24 publications
6
63
0
Order By: Relevance
“…All analyses strongly supported the Malagasy leaf chameleon genus Brookesia as the sister group to a large clade comprising all other chameleon genera, consistent with other recent studies that have incorporated nuclear DNA data [29,30,55].…”
Section: Results (A) Phylogeny and Datingsupporting
confidence: 71%
See 3 more Smart Citations
“…All analyses strongly supported the Malagasy leaf chameleon genus Brookesia as the sister group to a large clade comprising all other chameleon genera, consistent with other recent studies that have incorporated nuclear DNA data [29,30,55].…”
Section: Results (A) Phylogeny and Datingsupporting
confidence: 71%
“…Given these considerations, an African origin for chameleons is not only plausible, but is also consistent with the fossil record, present day distributions and oceanographic processes. Indeed, dated phylogenetic analyses using multiple markers and complete generic-level taxon sampling strongly suggest an Eocene out-of-Africa dispersal of one chameleon genus to the Seychelles [29], rather than the out-of-Madagascar dispersal previously proposed [14].…”
Section: Introductionmentioning
confidence: 99%
See 2 more Smart Citations
“…Of the currently described 202 chameleon species, 86 species belong to the four Malagasy genera Brookesia Gray, 1865, Calumma Gray, 1865, Furcifer Fitzinger, 1843, and Palleon Glaw, Hawlitschek & Ruthensteiner, 2013, and all but two Comorian species of Furcifer are endemic to Madagascar (Glaw 2015). Although the Seychelles chameleon, Archaius tigris (Kuhl, 1820), was included in the genus Calumma until recently, Townsend et al (2011) demonstrated that it represents a different African lineage and that Calumma is endemic to Madagascar. The Malagasy chameleons were relatively intensively studied in the past (Brygoo 1971(Brygoo , 1978, but still many new species are regularly dis-the type locality (Forêt de Tsararano).…”
Section: Introductionmentioning
confidence: 99%